2017
DOI: 10.1016/j.bbamem.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proteins structures: A review on computational modeling tools

Abstract: Even though MPs are elementary and important in nature, the determination of their 3D structure has proven to be a challenging endeavor. Computational methods provide a reliable alternative to experimental methods. In this review, we focus on computational techniques to determine the 3D structure of MP and characterize their binding interfaces. We also summarize the most relevant databases and software programs available for the study of MPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 325 publications
0
49
0
Order By: Relevance
“…Examples of this approach include the study of the lutropin receptor dimerization (Fanelli, 2007), studies aimed at characterizing the interaction interface in serotonin (5-HT) 4 (Bestel, 2005;Soulier et al, 2007) and rhodopsin complexes (Han et al, 2009), and the generation of models for the heterodimeric mGluR 2 -5-HT 2A complex (Bruno et al, 2009) and for the dopamine D 1 -D 2 receptor dimer ). -Molecular dynamics and coarse-grained simulations are one of the most versatile and widely applied computational techniques for the study of membrane proteins (Almeida et al, 2017), as they consider the tertiary structure of the studied proteins and can implement an energy landscape to estimate the molecular interactions, also accounting for the role of the lipid microenvironment. Such methods have also been used to study of GPCR dimerization and oligomerization (Fanelli et al, 2013;Jonas et al, 2015;Altwaijri et al, 2017).…”
Section: Interaction Interfacesmentioning
confidence: 99%
“…Examples of this approach include the study of the lutropin receptor dimerization (Fanelli, 2007), studies aimed at characterizing the interaction interface in serotonin (5-HT) 4 (Bestel, 2005;Soulier et al, 2007) and rhodopsin complexes (Han et al, 2009), and the generation of models for the heterodimeric mGluR 2 -5-HT 2A complex (Bruno et al, 2009) and for the dopamine D 1 -D 2 receptor dimer ). -Molecular dynamics and coarse-grained simulations are one of the most versatile and widely applied computational techniques for the study of membrane proteins (Almeida et al, 2017), as they consider the tertiary structure of the studied proteins and can implement an energy landscape to estimate the molecular interactions, also accounting for the role of the lipid microenvironment. Such methods have also been used to study of GPCR dimerization and oligomerization (Fanelli et al, 2013;Jonas et al, 2015;Altwaijri et al, 2017).…”
Section: Interaction Interfacesmentioning
confidence: 99%
“…Membrane proteins represent 25% of all human proteins (Dobson, et al, 2015;Gromiha and Ou, 2014) and perform essential roles in cellular functions. Approximately 50-60% of TM proteins are drug targets for various diseases (Almeida, et al, 2017;Overington, et al, 2006) and 90% of membrane proteins present disease-associated missense mutations that may affect protein folding, stability and function (Kulandaisamy, et al, 2019). Whole genome and exome sequencing have revealed that missense mutations that are mendelian and rare disease-causing are more frequent than previously thought and collectively affect millions of patients worldwide (Chong, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years other computational techniques have advanced significantly and protein structure prediction efforts can currently be grouped into those using ab initio methods (or ab initio guided approaches) and template-based methods (fold recognition and threading, comparative modelling) [20]. Currently, protein structure prediction remains a highly active and rapidly evolving area of research [2123]. …”
Section: Introductionmentioning
confidence: 99%